The Assumption of Dynamic Control of Psychosomatic Disorders in Children in the Treatment of Bronchial Asthma (Eurasian Journal of History, Geography and Economics, 2023)
In the formation of respiratory diseases with a psychosomatic component, as a stage in the development of the disease (for example, bronchial asthma (BA)), it is very important to clearly represent the contribution to the realization of the disease of the autonomic nervous system and the psychological characteristics of the child. Knowledge of the characteristics of child psychology is extremely important in understanding the formation of the somatic and mental health of a child-adolescentadult.